Murod Muhammad Do'st "Dasht-u dalalarda" hikoyasi - Barno Sotimova Botirali qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
In this article, the story "Dasht-u Dalalda" shows the experiences of the Uzbek nation, mental images, and issues of Uzbek character.